Community-Based Village Development Strategy Leveraging Social Capital: A Case Study of Lamongan Regency - Nalikan, Mohammad; ., Sumartono; ., Suryadi; Rozikin, Mochammad (Journal of Ecohumanism, 2025)
This study explores a village development strategy leveraging social capital, with Lamongan Regency as a case study, to foster inclusive, sustainable, and locally driven development. Social capital—comprising bonding, bridging, and linking—plays a pivotal role in facilitating interaction and collaboration both within the community and between the community and various stakeholders. This research adopts a qualitative approach with a descriptive method, utilizing data obtained through in-depth interviews, observations, and document analysis. The findings reveal that social capital in Lamongan Regency significantly contributes to strengthening community solidarity, enhancing public participation, and expanding access to resources and opportunities. The bonding dimension manifests in strong kinship and local solidarity, while bridging and linking facilitate cross-group collaboration and connections with formal institutions. The pentahelix collaboration model—engaging the government, communities, the private sector, academia, and the media—emerges as an effective approach to supporting the implementation of village development strategies. However, several challenges were identified, including suboptimal cross-sectoral program integration, limited technical support at the village level, and insufficient private sector participation in empowerment initiatives. This study recommends a development strategy that integrates social capital with policies rooted in collaboration and local innovation to enhance rural community welfare. By adopting a holistic and sustainable approach, this social capital-based development model presents a strategic solution for other regions facing similar challenges.